Perlindungan Hukum terhadap UMKM Akibat Review Makanan yang tidak Objektif: Analisis Normatif Berdasarkan KUH Perdata dan UU ITE - Putu Sri Widari Pradnyani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The development of digital media has made food reviews an important factor in shaping consumer perceptions and decisions, especially for Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector, which are highly dependent on reputation. However, food reviews that are not objective, not based on real experiences, or presented in an exaggerated manner have the potential to cause material and immaterial losses for MSMEs. This study aims to analyze the forms of legal protection for MSMEs due to biased food reviews in digital media and to examine the legal basis for liability for such reviews based on the Civil Code and the Electronic Information and Transactions Law. The research method used is normative juridical with a regulatory approach and conceptual through the analysis of primary and secondary legal materials. The results of the study show that MSMEs can take legal action through lawsuits for unlawful acts and criminal provisions in the ITE Law, although its implementation still faces obstacles in the form of the nature of complaint offenses and difficulties in proving them. This study emphasizes the need to strengthen regulations and ethical guidelines for digital reviews in order to provide more proportional legal protection for MSMEs.